2016
DOI: 10.1016/j.it.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Immune Dysfunction as a Cause and Consequence of Malnutrition

Abstract: Malnutrition, which encompasses under- and overnutrition, is responsible for an enormous morbidity and mortality burden globally. Malnutrition results from disordered nutrient assimilation but is also characterized by recurrent infections and chronic inflammation, implying an underlying immune defect. Defects emerge before birth via modifications in the immunoepigenome of malnourished parents, and these may contribute to intergenerational cycles of malnutrition. This review summarizes key recent studies from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
421
2
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(451 citation statements)
references
References 98 publications
(276 reference statements)
9
421
2
19
Order By: Relevance
“…In a clinical study, oxidative stress has been shown to be negatively and significantly associated with nutritional status . Furthermore, undernourishment has been well shown to be associated with impairment of immune function of the host . Some micronutrients are possibly of importance in protecting against reactivated TB, through anti‐oxidative and other mechanisms .…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical study, oxidative stress has been shown to be negatively and significantly associated with nutritional status . Furthermore, undernourishment has been well shown to be associated with impairment of immune function of the host . Some micronutrients are possibly of importance in protecting against reactivated TB, through anti‐oxidative and other mechanisms .…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
“…82 Furthermore, undernourishment has been well shown to be associated with impairment of immune function of the host. 83 Some micronutrients are possibly of importance in protecting against reactivated TB, through anti-oxidative and other mechanisms. 84,85 Interestingly, obesity appears to protect against development of TB.…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
“…Each of these early exposures can have lasting effects on physical and mental health, including altered stress response (Puetz et al, 2016; Rosen et al, 2004); increased inflammatory factors (Bourke, Berkley, & Prendergast, 2016; Coelho et al, 2014), and increased risk for cognitive and mental health problems (Galler et al, 2012; 2013; Young & Widom, 2014). In addition, they likely share some of the same risk factors, such as strained family economic resources (Brown et al, 1998; Walker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is known that nutritional changes may result in related immune parameters alterations [60], for instance, thymus relative weight [61,62], increased chronic inflammation susceptibility and recurrent infections [63].…”
Section: Discussionmentioning
confidence: 99%